2011
DOI: 10.1007/s13244-011-0112-5
|View full text |Cite
|
Sign up to set email alerts
|

Fatty liver deposition and sparing: a pictorial review

Abstract: ObjectiveFatty liver deposition is a very common finding, but it has many atypical patterns of distribution that can represent diagnostic pitfalls. The purpose of this pictorial essay is to review different patterns of fatty liver deposition and sparing.MethodsWe searched our archive retrospectively, reviewed the literature, and identified six patterns of liver steatosis.ResultsSteatosis may be diffuse, geographic, focal, subcapsular, multifocal or perivascular.ConclusionsPrevious knowledge of atypical pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 14 publications
1
55
0
Order By: Relevance
“…Even though many studies reported an association between liver fibrosis and hepatic iron overload [22,29] , we did not perform histopathological studies, since biopsy sample taking is not ethically justified in healthy individuals with no clinical indication. It should be noted that since deposition of iron and fat in liver can be heterogeneous [34] , samples obtained by biopsy may not necessarily represent the status of liver iron and fat in all sections of the liver. Of course, imaging evaluation of hepatic steatosis using MRI has been reported as a reliable alternative for the histological study of liver [35] .…”
Section: Discussionmentioning
confidence: 99%
“…Even though many studies reported an association between liver fibrosis and hepatic iron overload [22,29] , we did not perform histopathological studies, since biopsy sample taking is not ethically justified in healthy individuals with no clinical indication. It should be noted that since deposition of iron and fat in liver can be heterogeneous [34] , samples obtained by biopsy may not necessarily represent the status of liver iron and fat in all sections of the liver. Of course, imaging evaluation of hepatic steatosis using MRI has been reported as a reliable alternative for the histological study of liver [35] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several recent studies have used imaging methods to demonstrate that VAT, rather than subcutaneous abdominal fat (i.e. SAT), has more influence than BMI in terms of predicting the presence of NAFLD [94][95][96][97][98][99]. In one such study, obese subjects with hepatic steatosis had higher ratios of truncal:total body fat compared with similarly obese persons without fatty liver [95].…”
Section: Nonalcoholic Fatty Liver Disease Physical Activity and Adimentioning
confidence: 99%
“…In one such study, obese subjects with hepatic steatosis had higher ratios of truncal:total body fat compared with similarly obese persons without fatty liver [95]. Nevertheless, the sensitivity and specificity of available imaging methods for measuring liver fat content are unsatisfactory compared to proton ( 1 H) magnetic resonance spectroscopy; the latter modality is usually not available outside a research setting [97][98][99][100][101][102][103]. Conflicting results on the accuracy of different modalities have been 1.…”
Section: Nonalcoholic Fatty Liver Disease Physical Activity and Adimentioning
confidence: 99%
See 1 more Smart Citation
“…Fatty infiltration of the liver, often induced by chemotherapy, may further worsen US performance in this crucial task [4]. In particular, unusual and heterogeneous forms of fatty deposition, such as geographic liver fatty deposition, may prevent greyscale US from reliably ruling out the presence of liver metastases in cancer patients, even in the absence of any overt and/or suspect focal liver lesion [5]. More recently, the introduction of contrast-enhanced ultrasonography (CEUS) has led to a dramatic improvement in diagnostic accuracy of US in the detection of liver metastases, when compared to conventional greyscale US [2,6].…”
Section: Introductionmentioning
confidence: 99%